Lung Ventilation/Perfusion Scintigraphy for the Screening of Chronic Thromboembolic Pulmonary Hypertension (CTEPH): Which Criteria to Use? - Le Pennec, Romain; Tromeur, Cécile; Orione, Charles; Robin, Philippe; Le Mao, Raphaël; De Moreuil, Claire; Jevnikar, Mitja; Hoffman, Clément; Savale, Laurent; Couturaud, Francis; Sitbon, Olivier; Montani, David; et al. (Frontiers in Medicine, 2022)
The diagnosis of chronic thromboembolic pulmonary hypertension (CTEPH) is a major challenge as it is a curable cause of pulmonary hypertension (PH). Ventilation/Perfusion (V/Q) lung scintigraphy is the imaging modality of choice for the screening of CTEPH. However, there is no consensus on the criteria to use for interpretation. The aim of this study was to assess the accuracy of various interpretation criteria of planar V/Q scintigraphy for the screening of CTEPH in patients with PH. Methods: The eligible study population consisted of consecutive patients with newly diagnosed PH in the Brest University Hospital, France. Final diagnosis (CTEPH or non-CTEPH) was established in a referential center on the management of PH, based on the ESC/ERS guidelines and a minimum follow-up of 3 years. A retrospective central review of planar V/Q scintigraphy was performed by three nuclear physicians blinded to clinical findings and to final diagnosis. The number, extent (sub segmental or segmental) and type (matched or mismatched) of perfusion defects were reported. Sensitivity and specificity were evaluated for various criteria based on the number of mismatched perfusion defects and the number of perfusion defects (regardless of ventilation). Receiver operating characteristic (ROC) curves were generated and areas under the curve (AUC) were calculated for both. Results: A total of 226 patients with newly diagnosed PH were analyzed. 56 (24.8%) were diagnosed with CTEPH while 170 patients (75.2%) were diagnosed with non-CTEPH. The optimal threshold was 2.5 segmental mismatched perfusion defects, providing a sensitivity of 100 % (95% CI 93.6-100%) and a specificity of 94.7% (95%CI 90.3-97.2%). Lower diagnostic cut-offs of mismatched perfusion defects provided similar sensitivity but lower specificity. Ninety five percent of patients with CTEPH had more than 4 segmental mismatched defects. An interpretation only based on perfusion provided similar sensitivity but a specificity of 81.8% (95%CI 75.3-86.9%). Conclusion: Our study confirmed the high diagnostic performance of planar V/Q scintigraphy for the screening of CTEPH in patients with PH. The optimal diagnostic cut-off for interpretation was 2.5 segmental mismatched perfusion defects. An interpretation only based on perfusion defects provided similar sensitivity but lower specificity.